2009
DOI: 10.1105/tpc.109.067801
|View full text |Cite
|
Sign up to set email alerts
|

A Dual Role for the S-Locus Receptor Kinase in Self-Incompatibility and Pistil Development Revealed by an Arabidopsis rdr6 Mutation

Abstract: The coordinate evolution of self-incompatibility (SI) and stigma-anther separation, two mechanisms that promote crosspollination in plants, has been a long-standing puzzle in evolution and development. Using a transgenic self-incompatible Arabidopsis thaliana model, we performed screens for mutants exhibiting a modified SI response. A mutation in the RNAdependent RNA polymerase RDR6, which functions in trans-acting short interfering RNA (ta-siRNA) production, was found that simultaneously enhances SI and cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 53 publications
(72 reference statements)
0
57
1
Order By: Relevance
“…In this study, the approach herkogamous phenotype in wild-type A thaliana was only observed when ARC1 was expressed with the SCRb-SRKb construct, suggesting that SRKb with ARC1 is required for this trait. Interestingly, SRKb was previously found to cause a stigma exertion phenotype when expressed in the Arabidopsis mutant for the RNA-dependent RNA polymerase-6 (rdr6) (Tantikanjana et al, 2009). However, we do not know if the approach herkogamy phenotype that we observed in wild-type A. thaliana expressing ARC1 with SCRb-SRKb results from a related mechanism to that seen for the stigma exertion phenotype Numbers indicate the number of samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the approach herkogamous phenotype in wild-type A thaliana was only observed when ARC1 was expressed with the SCRb-SRKb construct, suggesting that SRKb with ARC1 is required for this trait. Interestingly, SRKb was previously found to cause a stigma exertion phenotype when expressed in the Arabidopsis mutant for the RNA-dependent RNA polymerase-6 (rdr6) (Tantikanjana et al, 2009). However, we do not know if the approach herkogamy phenotype that we observed in wild-type A. thaliana expressing ARC1 with SCRb-SRKb results from a related mechanism to that seen for the stigma exertion phenotype Numbers indicate the number of samples.…”
Section: Discussionmentioning
confidence: 99%
“…n = 10 for each line (where two stigmatic papillae per stigma for five stigmas were examined). resulting from SRKb expression in the mutant rdr6 background (Tantikanjana et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Col(Sb) stigmas display an intense SI response only in stage 12 floral buds and early stage 13 flowers, but subsequently exhibit breakdown of SI in older flowers (after stage 13) (3). As previously described (3,6), stage 14 Col(Sb) stigmas allowed the growth of numerous SCRb-pollen tubes that penetrated the wall of stigma epidermal cells (Fig. 1B).…”
Section: Resultsmentioning
confidence: 98%
“…As a result, ago7 mutants exhibit up-regulation of the TAS3 ta-siRNA targets Auxin Response Factors 3 and 4 (ARF3 and ARF4) (9-11), which belong to a family of genes encoding DNA-binding proteins that bind to auxin response elements in the promoters of auxin responsive genes (12). We had previously shown that ago7 plants exhibit enhanced SI and stigma exsertion phenotypes similar to those observed in rdr6 plants (6). These results suggested that positive regulators or effectors of SI and pistil development are regulated by ta-siRNA(s) and that ARF3 and/or ARF4 might function in SI.…”
mentioning
confidence: 99%
See 1 more Smart Citation